Guidelines for the Research of the Lithuanian Catholic Church Metrics Books - Garliauskas, Vidas (Bibliotheca Lituana, 2012)
The metrics books of the Lithuanian Catholic Church are a heritage treasure of the whole nation. Up until the 20th century there were approximately 600 churches in Lithuania and each church had more than a dozen metrics books on average which means there could be up to 10 000–15 000 metrics books remaining in various archives. Due to the soviet occupation the church archives were damaged and metrics books were scattered to various unclear locations. Due to these unfortunate historical situation metrics books research has only begun and the books themselves are not yet fully catalogued. Some research on metrics books has been done by Zigmas Zinkevičius, Vitalija Macijauskienė, Jonas Palionis and others. Historians have shed some light on metrics book archives in various archives. It is clear that individual important research work has been done but an overall targeted research is lacking. A priority objective is to create a state wide data base of all catalogued metrics books. Second steps would be complex research of the metrics books including creation of a theoretical information base, creation of various data bases, use of the metrics books for localized research and etc. Successful research of metrics books is only possible if specific guidelines are followed. That is why this publication includes methodical instructions for researches to use when uncertain situations are encountered. The publication includes two cases of metrics books research. In the first example a couple of unique excerpts are presented with comments. The second one reconstructs the picture of the Suginčiai (Molėtai district) estate and town community during the 17th century. It includes residents of the estate, newlyweds, families and other persons). Philological notes on names are also included.
Keywords: none